Vzhodnoazijska motivika lisic v delih Alme Karlin - Veselič, Maja (Poligrafi, 2022)
On her journey around the world, the global traveller and writer alma Karlin was most interested in the beliefs and practices of the countries she visited. She was particularly drawn to those that ? in the spirit of the times and of the contem-porary flourishing comparative religious studies ? she called superstitions, as they were said to transport the observers and readers into strange and foreign worlds. In East asia, the supernatural being that she found most fascinating was the fox, and in her unpublished text Glaube und Aberglaube im Fernen Osten (Faith and Superstition in the Far East) she particularly focussed on them. The fox is also one of the East asian religious elements, besides Buddhism, most commonly found in her literary works.This paper initially summarises the beliefs and narratives about foxes discussed by Karlin in the above-mentioned popular scientific text, and subsequently frames her notes in the complex world of the fox motif in China and Japan, which is an inextricable entanglement of popular religiosity, elements of folklore, and classical literary texts. The concluding section presents an analysis of the image of the fox in alma Karlin’s published short stories inspired by East asia. Her mention of foxes often serves to provide the events with a concrete geographical-cultural setting, while in the plots woven around fox spirits the latter appear as the classical literary motifs of unearthly beauties seducing young men, depriving them of reason, and sucking the life energy out of them, thus bringing them to the verge of death.
Keywords: Alma Karlin; beliefs; China; fox spirits; Japan; Japonska; Kitajska; lisice; literarna dela; literatura; literature; magical creatures; praznoverje; superstitions; verovanje; vraževerje; vzhodnoazijski religijski elementi